Economic Evaluation of Climate Change Impacts and Adaptation in Italy - Alessandra Goria; Gretel Gambarelli (Fondazione Eni Enrico Mattei (FEEM), 2004)
The paper deals with the social and economic dimensions of climate change impacts and adaptation in Italy. The ultimate aim of the paper is to provide policy makers and experts with a conceptual framework, as well as methodological and operational tools for dealing with climate change impacts and adaptation from an economic perspective. In order to do so, first a conceptual and theoretical framework of the economic assessment of climate change impacts is presented and the state of the art about impact assessment studies is briefly analysed. Then, the Italian case is taken into account, by underlying the main impacts and adaptation challenges that are likely to be implied by climate change in the next decades. The analysis of the Italian case is particularly addressed through the description of the methodology and results of two case studies. The first one, dealing mainly with impact assessment, is carried out at the national level and is part of a EC funded project on Weather Impacts on Natural, Social and Economic Systems (WISE). The second one is carried out at the local level and focuses on sea level rise impacts and adaptation in a plane south of Rome. The two case studies allow to propose simple and flexible methodologies for the economic impact assessment and the economic valuation of adaptation strategies.
Keywords: Q25; C5; C42; 330; Climate change; Economic impact assessment; Adaptation; Cost benefit analysis; Klimawandel; Kosten-Nutzen-Analyse; Soziale Kosten; Umweltkosten; Italien; Wirkungsanalyse